Effects of storage time and temperature on polyphenolic content and qualitative characteristics of freeze-dried and spray-dried bayberry powder. (May 2017) - Cheng, An-Wei; Xie, Hong-Xia; Qi, Yan; Liu, Chao; Guo, Xu; Sun, Jin-Yue; Liu, Li-Na
Abstract: To extend shelf-life and develop new bayberry products, the effects of storage time and temperature on polyphenolic content and qualitative characteristics of freeze-dried and spray-dried bayberry power were studied. Results showed that the retention of total polyphenols, gallic acid, protocatechuic acid, cyanidin-3-o-glucoside and anthocyanins in the freeze-dried bayberry powder was in most cases higher than in the spray-dried powder when they were stored for the same period. The content of these components in both the freeze-dried and spray-dried bayberry powder decreased gradually with the longer storage time. No significant difference was detected for the retention of these compounds whether they were stored at 4 °C or 25 °C. The browning index of both the freeze-dried and spray-dried powder significantly increased during a 50-day storage period. The ΔE value of the bayberry powder stored at 25 °C was distinctly higher than that of the other treated samples; a value of the spray-dried powder was slightly higher than that of the other samples. All presented results indicate that freeze-drying and 4 °C storage is an efficient and convenient method to maintain the bioactive polyphenolic components and high-qualitative characteristics of bayberry fruits. Highlights: The high retention of phenolic compounds was detected in freeze-dried bayberry powder. Longer storage time decreased gradually phenolic content in bayberry powder. The high value of a was detected in the spray-dried powder stored at 4 °C. Freeze-drying is a feasible way to keep high-qualitative characteristics of bayberry.